Occupational noise exposure and the effects on blood pressure of grass-cutting workers. Issue 1 (March 2021) - Kamaruzzaman, Afiqah; Ibrahim, Tengku Azmina; Sulaiman, Fazrul Razman; Ismail, Ismaniza
Abstract: This study aims to identify the determinants of key forces in the external and internal environment of event management to propose a sustainable environment analysis framework that will help organizers to improve the sustainability of the strategy formulation. The proposed framework incorporates sustainability practices, previous research on sustainable event management, existing strategies of sustainable strategic management, and the results from this study. This framework has adopted PEST Analysis (a framework used to analyse and monitor macro-environmental factors that may have a profound impact on an organization's performance) in external environment analysis and Mckinsey 7s Framework in internal environment analysis to identify sustainable-related determinants of key forces to propose common sustainable practices to get common acceptance for sustainability. The identified determinants were applied in the proposed framework to guide event organizer when identifying key forces of external and internal environment which can influence to achieve sustainability in the event. On top of this, SWOT Analysis (a strategic planning technique used to help an organization to identify strengths, weaknesses, opportunities, and threat related to business competition) was adopted to help event organizers to identify the opportunities and threats in the external environment and understand the strengths and weakness of the organization to formulate effective sustainable strategies and move their events toward sustainability.